2022
DOI: 10.3390/act11060171
|View full text |Cite
|
Sign up to set email alerts
|

Electromechanical Performance of Biocompatible Piezoelectric Thin-Films

Abstract: The present study analyzed a computational model to evaluate the electromechanical properties of the AlN, BaTiO3, ZnO, PVDF, and KNN-NTK thin-films. With the rise in sustainable energy options for health monitoring devices and smart wearable sensors, developers need a scale to compare the popular biocompatible piezoelectric materials. Cantilever-based energy harvesting technologies are seldom used in sophisticated and efficient biosensors. Such approaches only study transverse sensor loading and are confined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…The use of engineering techniques and models will significantly reduce the cost of modeling a real PS and not spend significant funds on new software packages and their extensions. So, according to information from the Internet, the cost of the COMSOL Multiphysics software product is 2,650,000 rubles [4,5].…”
Section: The Object Of the Study Is The Design Manufacturing Technolo...mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of engineering techniques and models will significantly reduce the cost of modeling a real PS and not spend significant funds on new software packages and their extensions. So, according to information from the Internet, the cost of the COMSOL Multiphysics software product is 2,650,000 rubles [4,5].…”
Section: The Object Of the Study Is The Design Manufacturing Technolo...mentioning
confidence: 99%
“…In the article [4] elastic elements with piezoelectric films formed on their surface are considered, as studies have shown, piezo films have a significant spread in electrophysical characteristics (EPC) and cannot measure static loads. In addition, the article does not specify methods for stabilizing EPC.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…36 In addition, many piezoelectric polymers, such as poly(vinylidene fluoride) (PVDF), along with its copolymers, such as poly[(vinylidene fluoride)-co-hexafluoropropylene] (PVDF-HFP) and poly[(vinylidene fluoride)-co-trifluoroethylene] (PVDF-TrFE), poly[(3-hydroxybutyric acid)-co-(3-hydroxyvaleric acid)] (PHBV), and poly(L-lactic acid) (PLLA), are generally considered to be highly biocompatible. [37][38][39] Combined with their flexibility, this biocompatibility makes these polymers particularly well suited for biomedical applications such as tissue engineering and modification of biological surfaces. Compared to piezoelectric ceramics and single crystals, piezoelectric polymers are also less expensive owing to their relatively simple and low-cost fabrication processes, such as solution casting, electrospinning, or additive manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…It also renders them practical for applications where a material needs to either conform to irregular surfaces or be stretched or compressed cyclically 36 . In addition, many piezoelectric polymers, such as poly(vinylidene fluoride) (PVDF), along with its copolymers, such as poly[(vinylidene fluoride)‐ co ‐hexafluoropropylene] (PVDF‐HFP) and poly[(vinylidene fluoride)‐ co ‐trifluoroethylene] (PVDF‐TrFE), poly[(3‐hydroxybutyric acid)‐ co ‐(3‐hydroxyvaleric acid)] (PHBV), and poly( l ‐lactic acid) (PLLA), are generally considered to be highly biocompatible 37–39 . Combined with their flexibility, this biocompatibility makes these polymers particularly well suited for biomedical applications such as tissue engineering and modification of biological surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed design uses polyvinylidene fluoride (PVDF) as the piezoelectric material. This polymeric piezoelectric material has lower piezoelectric coefficients compared to traditional piezoceramics or single-crystal piezoelectric materials [20], but allows for greater flexibility and lightweight that can better allow it to bend with the motion of the lead wire [21,22]. The design was modelled using finite element analysis in COMSOL Multiphysics ® v. 6.0 (COMSOL AB, Stockholm, Sweden) and verified with experimental testing.…”
Section: Introductionmentioning
confidence: 99%